Digitalization of Unimed Fine Arts Gallery Through Virtual Tour 360 for Accessibility and Exhibition - Purba, Rinanda; Adek Cerah Kurnia Azis; Kartono, Gamal; Amirulloh, Tifan Muhammad (Gorga : Jurnal Seni Rupa, 2025)
The limited accessibility to physical art galleries and the lack of comprehensive documentation of exhibitions have become challenges in preserving and promoting visual art in academic settings. Particularly in the Fine Arts Education Program at Universitas Negeri Medan (Unimed), the physical gallery space has yet to accommodate wider audience engagement, especially in digital formats. This creates a gap between the potential of technological integration and the current practices in art exhibition and education. Addressing this issue, this study aims to explore the digitalization of the Fine Arts Gallery through the development of a virtual tour as an effort to increase accessibility and improve exhibition documentation. The research employs a descriptive qualitative method with a case study approach, focusing on the process of designing and implementing a 360-degree virtual gallery experience. Data were collected through observations, interviews with lecturers, students, and gallery visitors, and open-ended surveys to capture perceptions and experiences. The findings reveal that the virtual tour not only provides broader access to art exhibitions beyond physical limitations but also enhances the visual and archival quality of gallery content. Furthermore, users perceive the platform as more engaging and educational. In conclusion, the digitalization of the gallery using virtual tour technology serves as a strategic innovation to support art learning, appreciation, and preservation in higher education. This approach may serve as a replicable model for other academic institutions seeking to modernize their art exhibition practices.